2017
DOI: 10.3920/bm2017.0009
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerance of three probiotic strains in healthy infants: a multi-centre randomized, double-blind, placebo-controlled trial

Abstract: Some strains of species belonging to the genera Bifidobacterium and Lactobacillus are used in order to maintain health. Although these organisms have a long record of safe use, it is important to assess their safety and tolerance in potentially vulnerable populations, such as infants. The objective of this study was to evaluate the safety and tolerance of three probiotic strains (Bifidobacterium longum subsp. infantis R0033, Bifidobacterium bifidum R0071 and Lactobacillus helveticus R0052) in healthy infants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Healthy term infants were enrolled (n = 208; 3 to 12 months of age) and received B. infantis R0033 (3 billion CFU/d; Lallemand Health Solutions, Montreal, Canada) over an eight week feeding period [54]. Other study groups included L. helveticus and B. bifidum.…”
Section: B Infantis R0033mentioning
confidence: 99%
“…Healthy term infants were enrolled (n = 208; 3 to 12 months of age) and received B. infantis R0033 (3 billion CFU/d; Lallemand Health Solutions, Montreal, Canada) over an eight week feeding period [54]. Other study groups included L. helveticus and B. bifidum.…”
Section: B Infantis R0033mentioning
confidence: 99%
“…Finally, a 2017 placebo‐controlled, parallel‐group study was performed on 221 healthy infants who received placebo or one of three different probiotic strains for eight weeks, namely Bifidobacterium longum subspecies infantis R0033, Bifidobacterium bifidum R0071 or Lactobacillus helveticus R0052. Their urinary d ‐lactate levels were below the quantification limit of the method in all of the groups, and there were also no differences between the groups with regard to anthropometric measurements .…”
Section: Resultsmentioning
confidence: 87%
“…We identified five randomised controlled trials from 2005 to 2017 covering 544 healthy infants from one day to 12 months of age. These all included d ‐lactate concentration measurements and lactic acid‐related outcome assessment in infants receiving d ‐lactate producing probiotic strains . Table summarises the characteristics of all the RCTs we included.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the sustained effect in time observed after intake cessation could be explained by the timing of administration; childhood is a critical window for the immune system maturation. Indeed, this probiotic formulation strengthens the immune system and promotes host defence development on three fronts: counteracting opportunistic pathogens, maintaining the integrity of the intestinal barrier, and modulating cellular and systemic immunity [23][24][25][26][27][31][32][33]. In rodents, probiotic formula we used in the study induced tight junction proteins expression and mucin production, which contributes to the maintenance of intestinal permeability [34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Strain persistence was not assessed in the stools and we did not assess the levels of immunoglobulins in the population; this information could have allowed to confirm the mechanism behind the lasting effect of probiotic prophylaxis. However, long-term colonization of the intestinal tract is unlikely; generally, probiotics are no longer detected in stools within a month after intake cessation [32]. Additionally, the cause of the primary URTI infec-tions was not determined.…”
Section: Resultsmentioning
confidence: 99%